2005
DOI: 10.1021/jo0508189
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies toward Aryl-(4-aryl-4H-[1,2,4]triazole-3-yl)-amine from 1,3-Diarylthiourea as Urea Mimetics

Abstract: A thiophile promoted synthesis of di-substituted 4H-[1,2,4]triazole-3-yl-amines as urea mimetics from the corresponding 1,3-disubstituted thioureas has been studied and the scope and limitations of this reaction are presented. The reaction proceeds through the formation of a carbodiimide, followed by a sequential addition-dehydration with acyl hydrazides. 1,3-Branched dialkylthioureas result in the formation of the corresponding ureas. The electronic and steric effect of the substitution on the phenyl rings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…These results indicate a distinct recognition mechanism of 4 towards Cu 2 + as compared to that of its response to Hg 2 + . Recently, Chorev et al [26] have reported that dialkyl-substituted thioureas undergo rapid formation of the intermediate carbodiimide in the presence of HgA C H T U N G T R E N N U N G (OAc) 2 (Scheme 4). Thus, we can deduce a recognition mechanism of 4 towards Hg 2 + as follows (Scheme 3): a) In the presence of less than one equiv Hg 2 + , 4 undergoes an irreversible desulfurization reaction and is thereby converted into an intermediate carbodiimide 7, in accordance with the observations of Chorev et al [26] This is further confirmed by the appearance of a peak at m/z 538.2 (calcd for 538.3) assigned to [7+H] + in the ESI mass spectrum of a colorless and weakly fluorescent mixture of 4 with 0.5 equiv of Hg 2 + in ethanol (see Figure S10 in the Supporting Information).…”
Section: Hgmentioning
confidence: 99%
“…These results indicate a distinct recognition mechanism of 4 towards Cu 2 + as compared to that of its response to Hg 2 + . Recently, Chorev et al [26] have reported that dialkyl-substituted thioureas undergo rapid formation of the intermediate carbodiimide in the presence of HgA C H T U N G T R E N N U N G (OAc) 2 (Scheme 4). Thus, we can deduce a recognition mechanism of 4 towards Hg 2 + as follows (Scheme 3): a) In the presence of less than one equiv Hg 2 + , 4 undergoes an irreversible desulfurization reaction and is thereby converted into an intermediate carbodiimide 7, in accordance with the observations of Chorev et al [26] This is further confirmed by the appearance of a peak at m/z 538.2 (calcd for 538.3) assigned to [7+H] + in the ESI mass spectrum of a colorless and weakly fluorescent mixture of 4 with 0.5 equiv of Hg 2 + in ethanol (see Figure S10 in the Supporting Information).…”
Section: Hgmentioning
confidence: 99%
“…In the case of compounds 4d,f, the NH group signal is found at 9.10-9.20 ppm as a singlet. Such a downfield shift is characteristic for some derivatives of N-aryl-N-(1,2,4-triazol-3-yl)amines [13]. The structure of intermediates 3 was demonstrated for thiosemicarbazide 3e, which could be separated and characterized.…”
mentioning
confidence: 89%
“…Derivatives of 1,2,4-triazole have found common use in medicine [1-3] and as efficient corrosion inhibitors [4], catalysts [5], ligands [6], and chemosensors [7], Various pathways and methods exist for the synthesis and modification of both 1,2,4-triazole [8][9][10] and its 3-thio derivatives [11][12][13]. Greatest interest is found for one-and two-step methods for the preparation of similar structures.…”
mentioning
confidence: 99%
“…13 When 1,3-disubstituted thiourea was reacted with formic hydrazide and mercury(II) acetate as thiophile, the reaction mixture produced acyl hydrazide adduct, which was cyclized to the corresponding [1,2,4]triazole under acidic conditions. …”
Section: (D) Synthesis Of N-substituted 2-amino Benzimidazoles and Bementioning
confidence: 99%